2021
DOI: 10.3389/fgene.2021.721556
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in the Diagnosis and Prognosis of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) pandemic triggered an unprecedented global effort in developing rapid and inexpensive diagnostic and prognostic tools. Since the genome of SARS-CoV-2 was uncovered, detection of viral RNA by RT-qPCR has played the most significant role in preventing the spread of the virus through early detection and tracing of suspected COVID-19 cases and through screening of at-risk population. However, a large number of alternative test methods based on SARS-CoV-2 RNA or proteins or host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 93 publications
2
60
0
Order By: Relevance
“…The authors found consistent disruptions in glucose metabolism and dysregulation in the TCA and urea cycles which were identified as potential targets for therapeutic intervention ( figure 1a ). These metabolomics changes are consistent with metabolomics studies in other contexts and point to an underlying bioenergetic crisis as a key pathogenic feature of COVID-19 [ 5 ].…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The authors found consistent disruptions in glucose metabolism and dysregulation in the TCA and urea cycles which were identified as potential targets for therapeutic intervention ( figure 1a ). These metabolomics changes are consistent with metabolomics studies in other contexts and point to an underlying bioenergetic crisis as a key pathogenic feature of COVID-19 [ 5 ].…”
supporting
confidence: 85%
“…More recent studies have begun to associate metabolomics changes with symptoms representing specific organ system failures – for example, the acute delirium and post-recovery mental health issues of the nervous system and disruptions of the digestive system [ 6 , 7 ]. Dysregulation of the kynurenine pathway has been among the most consistent findings as reported in numerous, independent studies [ 5 ]. Of potential significance is that many of the metabolomics abnormalities in COVID-19 are similar to those found in sepsis and acute respiratory failure, suggesting a common mechanism leading to an acute bioenergetic crisis [ 8 , 9 ].…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The results indicate that Covid 19 severity is associated with a decline in tryptophan (Trp) reflecting immune dysregulation. Early evidence that tryptophan metabolism regulated immunity (D) has more recently led to the observation that kynurenine/tryptophan ratios correlate with carbohydrate metabolism and cardio-metabolic risk [ 23 ] both associated with COVID-19 severity [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomics in COVID-19 patients proofed the existence of a characteristic immune-metabolic signature [ 34 , 35 , 36 ] with marked alterations in nitrogen metabolism, amino acid homeostasis, catabolism, transamination, and carbon metabolism affecting glucose and free fatty acids levels [ 34 ]. The metabolites in these affected pathways correlated with the increased IL-6 and CRP concentrations [ 34 ].…”
Section: Discussionmentioning
confidence: 99%